Pentingnya Pendidikan Karakter dalam Islam: Membangun Identitas dan Moralitas Mahasiswa - Hernawati; Mulyani, Dewi (Andragogia: Journal Education Science And Islamic Studies, 2025)
Character education in Islam is crucial for building the identity and morality of students. This article discusses how Islamic values can be integrated into higher education to create moral and integrity-driven individuals. Using a case study method, this research explores various character education programs implemented in Islamic campuses and their impact on student behavior. The findings indicate that the application of character education based on Islamic teachings significantly enhances students' moral awareness and social responsibility. In conclusion, character education in Islam not only shapes students' identities but also prepares them to contribute positively to society.